Recognitive Justice and Educational Inequalities: An Intersectional Approach Involving Secondary Grade School Students in Greece - Christos Govaris; Wassilis Kassis; Dimitris Sakatzis; Jasmin-Olga Sarafidou; Raia Chouvati (MDPI AG, 2021)
Adopting the theoretical approach of recognitive justice and the degree of students' recognitive experiences regarding empathy, respect, and social esteem, the present study focused on educational inequalities in the multicultural school and the factors that affect their appearance and reproduction. We examined the existence of social relations' differences in a sample of 1303 students from 69 secondary schools in Greece, using a questionnaire constructed to investigate students' recognitive experience of their relationships with teachers. By applying an intersectional approach, mainly through multiple regression analysis and multivariate interaction tests with MANOVA, we were able to identify that migrant students and students from families with a low educational level experienced a significantly lower degree of recognition, mainly with the forms of respect and social esteem, both in their relationships with teachers and with peers. Additionally, levels of recognition among teachers explained the large amount of variability in academic achievement and self-esteem, while higher levels of recognition among peers were a significant predictor of the respective students' higher self-esteem. These deficits in recognition concern pedagogical practices that deprive these groups of students of opportunities and possibilities for equal participation in teaching and school life.